2021
DOI: 10.1021/acscentsci.1c00119
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Charged Complexes of Random Copolymers for the Segregation of Organic Molecules

Abstract: Nature harnesses the disorder of intrinsically disordered proteins to organize enzymes and biopolymers into membraneless organelles. The heterogeneous nature of synthetic random copolymers with charged, polar, and hydrophobic groups has been exploited to mimic intrinsically disordered proteins, forming complexes with enzymatically active proteins and delivering them into nonbiological environments. Here, the properties of polyelectrolyte complexes composed of two random copolymer polyelectrolytes are studied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…RHPs can have batch-to-batch variations but cannot yet be sequenced with monomeric specificity. Despite key differences, several computational and experimental studies have demonstrated the ability for RHPs to recapitulate protein-like behaviors. Unlike sequence-specific heteropolymers, the lack of RHP sequence information significantly hampers our ability to further leverage the full potential of this unique class of polymers for precisely tailored functionality. Synthetic breakthroughs in reversible-deactivation radical polymerization (RDRP) have made it possible to synthesize heteropolymers with improved reproducibility and control over the probability of each monomer along the polymer chain. This narrows the gap between theoretically ideal polymerization and synthesized heteropolymers.…”
Section: Introductionmentioning
confidence: 99%
“…RHPs can have batch-to-batch variations but cannot yet be sequenced with monomeric specificity. Despite key differences, several computational and experimental studies have demonstrated the ability for RHPs to recapitulate protein-like behaviors. Unlike sequence-specific heteropolymers, the lack of RHP sequence information significantly hampers our ability to further leverage the full potential of this unique class of polymers for precisely tailored functionality. Synthetic breakthroughs in reversible-deactivation radical polymerization (RDRP) have made it possible to synthesize heteropolymers with improved reproducibility and control over the probability of each monomer along the polymer chain. This narrows the gap between theoretically ideal polymerization and synthesized heteropolymers.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative hypothesis is that the random copolymers interact favorably with the substrate, leading to an increase in local substrate concentration. Indeed, it has been shown that these random copolymers can bind hydrophobic small molecules ( 41 ) and that IDRs in proteins, similar to the random copolymers in Fig. 4 B , promote higher-order assembly ( 62 ).…”
Section: Resultsmentioning
confidence: 86%
“…Due to their methyl methacrylate backbone, they are inexpensive to randomly polymerize in large-scale, industrial processes. They have also been used in previous computational and experimental studies of polymer complexes with proteins including horseradish peroxide, glucose oxidase, and organophosphorus hydrolase as well as small organic molecules ( 32 , 41 ). Further, amphiphilic random copolymers are well suited to complex with the heterogeneous polar and nonpolar surfaces of proteins ( 42 ) including PETase.…”
mentioning
confidence: 99%
“…More recently, a combined experimental and modeling approach has been developed in our group to segregate organic molecules in water by using polyelectrolyte complexes composed of random copolymers. 22 Clearly, the chemical diversity of protein surface patterns and the experimental challenges of tailored polymer design often prevent the development of general and sustainable protocols for an effective protein coassembly with random copolymers. Therefore, although some attempts have manifested promising scenarios, the prediction of the enzyme−random copolymer self-assembly conformation based on their physical-chemistry properties remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Successful results in this direction have been obtained by Panganiban and co-workers who presented an efficient design approach of random heteropolymers based on protein surface patches while maintaining the enzymatic activity in a foreign environment. More recently, a combined experimental and modeling approach has been developed in our group to segregate organic molecules in water by using polyelectrolyte complexes composed of random copolymers . Clearly, the chemical diversity of protein surface patterns and the experimental challenges of tailored polymer design often prevent the development of general and sustainable protocols for an effective protein coassembly with random copolymers.…”
Section: Introductionmentioning
confidence: 99%